Preventing the Emergence of Ebola Disease in Unaffected Countries: Necessity of Preparedness - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Kerman University of Medical Sciences, 2014)
The outbreak of Ebola disease in West-African nations have come as a wake-up call for the international health agencies and the public health authorities of the affected nations as well (1). This outbreak has shown to the world that even a disease which is almost forty years old, and which was detected on at-least twenty different occasions in different nations and was successfully contained every time, can still create havoc to such an extent that eventually it had to be declared an international public health emergency (2,3). It has been realized that the existence of an effective public healthcare delivery system is a must to successfully counter the disease outbreaks, and is extremely difficult to develop such systems after the crisis has occurred, and absence of the same can allow even a less infectious disease (viz. moderately long incubation period, individuals being non-infectious during the incubation period, absence of airborne transmission - all factors which do not favor rapid transmission) to grow at an exponential rate (4,5).